Prescottia ecuadorensis: a new species of Prescottia (Cranichidinae, Orchidaceae) from Ecuador - de Azevedo, Cecília O.; van Den Berg, Cássio (Phytotaxa, 2015)
Prescottia ecuadorensis, a new orchid species from Loja, Ecuador, is described.